Is your playing field unleveled? U.S. defense contracts and foreign firm lobbying - Kim, Jin Hyung (Strategic Management Journal, 2019)
Abstract Research Summary Prior research in political strategy shows that political capital is critical in achieving desirable nonmarket strategy outcomes. Less attention has been paid to the fact that firms vary in their ability to acquire political capital. Foreign firms, which typically suffer from the liability of foreignness, have difficulty acquiring and strengthening political capital in a host country. Drawing on the literatures on political capital, the liability of foreignness, and certification, I argue that relying on outside political capital—that is, hiring outside lobbyists—helps foreign multinational enterprises (MNEs) achieve better nonmarket outcomes, thanks to outside lobbyists' certifying role as political insiders. Empirically, the study examines U.S. Department of Defense weapons‐system prime contracts awarded to 20,301 U.S. and foreign‐owned defense contractors from 1998 through 2006. This study has theoretical and practical implications for studies on political capital, international business, and nonmarket strategies. Managerial Summary Political capital is assumed to be critical in nonmarket strategy to achieve positive firm outcomes, particularly in industries where political and regulatory players play an important role. However, due to certain industry or firm characteristics, some firms are at a disadvantaged position in acquiring and consolidating the political capital they need. In this research, I argue that one of the factors creating such disadvantage is foreignness. The results indicate that for those foreign firms with a liability of foreignness, relying on outside lobbyists is beneficial to overcome the disadvantages and to achieve better nonmarket outcomes because outside professional lobbyists can ease information flows between political and regulatory players and foreign firms through their trustworthiness as political insiders.